Juvenile idiopathic inflammatory myopathies assessment by magnetic resonance imaging: a scoping review of protocols, scoring systems, and applications - Paula, Vitor Tavares; Omori, Clarissa Harumi; Shinjo, Samuel Katsuyuki; Araújo, Daniel Brito de; Day, Jessica; Schiffenbauer, Adam; Magalhães, Claudia Saad [UNESP]; Conticini, Edoardo; Marrani, Edoardo; Guimarães, Julio Brandão; Rider, Lisa G.; Essouma, Mickael; et al. (Springer Nature, 2025)
BackgroundOur review assessed whole body (WB) and dedicated body-part magnetic resonance imaging (DedMRI) techniques, protocols, and inflammatory scoring systems, focusing on their clinimetric properties (reliability, validity, responsiveness) in clinical and research settings of patients with juvenile idiopathic inflammatory myopathies (JIIM).MethodsA comprehensive search of MEDLINE, EMBASE, and Cochrane databases from 2000 to 2024 identified relevant studies.ResultsSixteen studies enrolling JIIM patients with MRI were reviewed, which showed heterogeneity in objectives, methodologies, and scoring systems. Four (25%) studies used quantitative assessments, while 12 (75%) employed semi-quantitative or qualitative methods in scoring MRI. WB-MRI was performed in 3 (18.7%) studies, and DedMRI in 13 (81.2%). Muscle evaluation included assessments of edema [14 (87.5%) studies], fatty infiltration [4 (25%) studies], and atrophy [6 (37.5%) studies]. T1 images were used in 9 (56.2%) studies for measuring chronic changes, with coronal views reported in 6 (37.5%). Fluid-sensitive sequences (T2 with fat saturation, STIR) were employed in all studies and were obtained in the coronal plane in 9 (56.2%). These sequences were crucial for detecting soft tissue edema related to acute/subacute inflammation. One (6%) study included diffusion and T1 post-contrast sequences.ConclusionThere is significant heterogeneity in MRI protocols for evaluating JIIM. Standardized WB-MRI protocols are needed to ensure consistency and comparability across studies and institutions, optimize assessments of disease activity, treatment response, and follow-up in JIIM patients. Standardization should enhance the reliability of MRI for diagnosing and monitoring JIIM in clinical and research settings.